sistem manajemen kinerja: literature review dan agenda untuk penelitian selanjutnya - Wirdhawan, Rhanni Apriani; Wibisono, Dermawan (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
This study aims to determine the development of research related to designing an organization's performance management system. This study conducts a literature review on papers that have been published and are available in the Google Scholar and Proquest database with a time span of January 2012 to December 2022. Keywords such as performance management, design performance management, and performance management system were used. The results of this research use 10 papers that are considered capable of explaining methods for designing performance management systems. Keywords— Performance management system; Performance management; Approach; Literature review